Left prefrontal transcranial direct-current stimulation reduces symptom-severity and acutely enhances working memory in schizophrenia. (11th June 2021) - Meiron, Oded; David, Jonathan; Yaniv, Asaf
Highlights: tDCS add-on treatment alleviated illness-severity in schizophrenia. tDCS add-on treatment acutely improved verbal WM performance in SZ patients. Patients' post active-tDCS WM scores were comparable to healthy controls. Abstract: Recent studies indicated that left dorsolateral prefrontal cortex (DLPFC) transcranial direct current stimulation (tDCS) may improve clinical status and cognitive functioning in schizophrenia patients. The current study examined the effects of left prefrontal anodal tDCS on symptom-severity and on working memory performance in schizophrenia (SZ) patients. We conducted a double-blind, randomized sham-controlled parallel-group trial. Following baseline clinical and WM assessments, 19 chronic SZ patients were randomly assigned to receive 10 sessions of either active left dorsolateral prefrontal cortex (DLPFC) tDCS or sham DLPFC-tDCS across five consecutive days, followed by post-tDCS assessments every four weeks across 12 weeks. Active tDCS significantly alleviated symptom-severity versus baseline and versus sham tDCS. WM-performance improved versus baseline in the active tDCS group. Patients' symptom alleviation was maintained for four weeks after tDCS intervention. Patients' Post-tDCS WM scores were comparable to healthy controls' WM scores. The present findings highlight the benefits of left-prefrontal tDCS interventions and support the association between DLPFC dysfunction and symptom-severity in schizophrenia.